TRANSFORMASI PEMBELAJARAN BIOLOGI MELALUI MICRO LEARNING BERBASIS KONSEP DAN DATA ILMIAH - A.A. Istri Mirah Dharmadewi; Marinto Rengge; Suhaeli (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2026)
The transformation of biology learning in the digital era requires innovative approaches that integrate conceptual understanding with scientific data analysis. Biology learning should not only focus on theoretical concept mastery but also develop students’ ability to interpret data as part of the scientific process. This article aims to examine the implementation of micro learning based on concepts and scientific data as a strategy to transform biology learning. The study employs a conceptual-reflective approach by analyzing the characteristics of biology materials, the role of scientific data in learning, and the potential of micro learning to present concepts and data in concise and focused learning units. The results indicate that micro learning enables the gradual presentation of biological concepts while facilitating data interpretation through visual representations such as graphs, tables, and simplified diagrams. This approach helps students understand the relationship between biological concepts and empirical evidence. In addition, it supports the development of scientific literacy and numeracy skills, which are essential competencies in modern education. Therefore, concept and scientific data-based micro learning has the potential to become an effective strategy in transforming biology learning to be more meaningful, contextual, and relevant to the demands of digital-era education.